Poço de infiltração para controle de enchentes na fonte: avaliação das condições de operação e manutenção - Barbassa, Ademir Paceli (2014)
This study investigated the following aspects regarding a soakaway, i.e. an infiltration well: i) entrance filter device; ii) permeability of the geotextile; and iii) emptying time. The 3.6 m³ infiltration well drains a roof area of 241.8 m². The entrance device is made up of layers of sand, gravel and geotextile set on a metal structure. The concrete rings that form the lateral walls were covered with geotextile, and bricks were laid between the soil and concrete rings. The infiltration well remained in operation during the entire testing period, and specific events were simulated to measure the emptying time. Permeability and fine particle tests were carried out after eight months of operation. Samples of geotextile taken from the bottom, the walls and the entrance device presented average permeability reductions of approximately 50.7%, 7.7% and 21.2%, respectively. The sand in the entrance device retained around 34.8% of fine particles and the gravel retained 0.13% in the same period. The infiltration rate was approximately 34.7 mm/h. The R2 coefficient for measured and calculated times was 0.97.